Large Gastric Lipoma - Sharma, Barun Kumar; Dhakal, OP (Kathmandu University Medical Journal, 2013)
Gastric lipoma is a rare benign tumor and seen in five percent of gastro-intestinal lipomas and accounts for less than one percent of all gastric tumors. Gastric lipomas are located submucosally and usually in antral region of Stomach. Computed tomography is considered as valuable tool in the diagnosis of gastrointestinal lipomas. Due to their relative rarity, gastric lipomas are often left out of the differential diagnosis for upper gastro-intestinal submucosal masses. We report a case of 70 year female that presented with upper abdominal pain since last two years. Abdominal Computed tomography revealed a large gastric lipoma in antral region. Patient refused for any surgical intervention due to old age. Patient was provided symptomatic treatment and was under regular follow-up. Kathmandu University Medical Journal | VOL.10 | NO. 3 | ISSUE 39 | JUL- SEP 2012 | Page 70-72 DOI: http://dx.doi.org/10.3126/kumj.v10i3.8024